Sequential Observation of Implanted Endometriosis by Laparoscopy in Rats: Correlation Between the Prevalence Rate and the Estrous Cycle - Masayuki Uchida; Orie Kobayashi (Elsevier, 2013)
Abstract.: This study aimed to clarify the correlation between the estrous cycle and prevalence rate of endometriosis by sequential laparoscopy in Wistar-Imamichi female rats. The peritoneal implantation of endometrial tissue was performed in four estrous cycle rats (proestrus, estrus, metestrus, and diestrus). One week after implantation, the volume of the ectopic endometriosis was measured, and sequential laparoscopy was performed for 4 weeks to observe the prevalence rate. Five weeks after implantation, the volume of the ectopic endometriosis was measured again after laparoscopy. One week after implantation, the volume of endometriosis was significantly larger in proestrus and estrus rats than metestrus and diestrus rats. Prevalence rate was decreased with time. Five weeks after implantation, the prevalence rate and volume were higher and larger in the metestrus, diestrus, and estrus rats than in the proestrus rats. These results show that the estrous cycle affects the change of ectopic endometriosis. The decrease of prevalence rate was slow in metestrus, diestrus, and estrus rats as compared to that in proestrus rats. The volume of ectopic endometriosis showed little decrease with time when the endometrial tissue was implanted during the metestrus and diestrus portion of the cycle. Moreover, sequential laparoscopy made it possible to observe the prevalence rate of endometriosis. Keywords:: estrous cycle, experimental endometriosis in rat, laparoscopy, prevalence rate, volume of ectopic endometriosis